Gross Domestic Regional Product Reconciliation and Compilation Application Development in Sulawesi Selatan - Dimas Tresna Suhartono (Jurnal Mantik, 2020)
GDRP compilation in Indonesia is carried out using a mixed method between the top-bottom and bottom-up methods. The use of these methods resulted in inevitable statistical discrepancies. Regencies/municipalities GDRP reconciliation along with province is carried out annually to maintain the value of these statistical discrepancies. The collection/compilation of main tables of GDRP of regencies/municipalities along with provinces is still carried out in the conventional way, as well as in the reconciliation process. The development of information technology and e-Government encourages the implementation of information technology to increase the effectivity and efficiency of internal operations in the government, including the compilation and reconciliation process of this GDRP. Application development with the prototyping method for the compilation and reconciliation process can be a solution to conventional methods that are still in use. The GDRP reconciliation and compilation application that was built has been used by the BPS-Statistics of Sulawesi Selatan Provinceand can be duplicated elsewhere.